Implementation of Murabahah Financing in Improving the Welfare of UMKM (Study at BSI Bank) Batam City - Afi Parnawi; Andre Mirza Hartawan; Amrizal (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to investigate the implementation of murabahah financing by Bank Syariah Indonesia (BSI) in improving the welfare of Micro, Small and Medium Enterprises (MSMEs) in Batam City. In the context of Sharia economics, murabahah financing has become an important alternative for MSMEs to obtain funds without involving riba (interest) which is prohibited in Sharia principles. The research method used is a case study with a focus on murabahah financing services provided by Bank BSI. The research results show that murabahah financing from Bank BSI has had a positive impact on the welfare of MSMEs in Batam City. MSMEs that received murabahah financing from BSI Bank have experienced an increase in business capital, business expansion and increased production. Another advantage is the consultation and support services in business development provided by BSI Bank. However, this research also identified several challenges in implementing murabahah financing, such as sometimes complicated requirements and administrative obstacles. Therefore, recommendations are given to Bank BSI and the local government to continue to improve ease of access, provide better education, and improve coordination with MSMEs.